(untitled) (International journal of artificial intelligence, 2025)
The Popov–Godon phenomenon represents a specific form of periodontal pathology in which, despite significant alveolar bone loss, the interdental papillae and gingival bridges remain intact, creating an illusion of periodontal stability. In traditional clinical practice, this condition is often regarded as an indication for the extraction of mobile teeth followed by prosthetic rehabilitation. However, contemporary trends in periodontology emphasize the need to explore less invasive and more organ-preserving treatment options.This article examines alternative approaches to managing the Popov–Godon phenomenon, including the use of autologous plasma preparations (PRF/PRP), guided tissue regeneration, laser and photodynamic therapy, microimplants, and orthodontic tooth stabilization techniques. The case is made for a multidisciplinary and individualized treatment approach that may delay radical interventions and help preserve the functional integrity of the dentoalveolar system. Emphasis is placed on the regenerative potential of modern technologies and the importance of their integration into clinical protocols.